Tackling Displacement - Shahzar Raza Khan (American Journal of Islam and Society)
Akbar Allahabadi (1846-1921) was an influential Muslim Urdu-Persian poet of colonial India.1 He was born in 1846 in a town near Allahabad as Syed Akbar Hussain, and he belonged to a socially affluent family that had migrated from Iran.2 In keeping with the practices of the time, he learned Arabic and Persian in Allahabad, where his mother had moved in 1855.3 The name of the city then became the surname by which he is known. In 1856, he also enrolled in the Jumna Mission School, though he dropped out before completing his studies in 1859.4 Meanwhile, he managed to learn English, which enabled him to study Western philosophy and ensured that he could, with ease, frequently use English words and idioms in his Urdu poetry. He took up a clerkship in a government office after leaving school5 and, in 1866, passed an exam to become a barrister.6 After two years, in 1868, he became a Tahsildar (sub-district collector), qualifying as a lawyer at the High Court in 1874.7 Finally, in 1880, he became a Sessions Court Judge, a position he would hold until 1903, when he retired due to worsening eye-sight.8 This would also be the height of his professional career, and the title of Khan Bahadur was awarded to him by the British Government for his services in 1895.9 After his retirement he resided in Allahabad until his passing in 1921.10